„Humbug und Taktlosigkeit“ oder „ein anlockendes Aushängeschild“ Alexander von Humboldt als Held einer Novelle – 1858 - Ingo Schwarz (HiN - Alexander von Humboldt im Netz. Internationale Zeitschrift für Humboldt-Studien, 2007)
Article in German, Abstracts in English and GermanThis paper deals with a novella published in 1858, in which Alexander von Humboldt appeared as the title hero. The author, a Prussian officer named Eugen Hermann von Dedenroth, sent Humboldt a copy of his book hoping to receive a positive response. However, Humboldt was so angry that he published a letter complaining about the novella's lack of respect for him and his career.